Sandy Lake Health and Diabetes Project: A Community-Based Intervention Targeting Type 2 Diabetes and Its Risk Factors in a First Nations Community - Kakekagumick, Kara E.; Naqshbandi Hayward, Mariam; Harris, Stewart; Saksvig, Brit; Gittelsohn, Joel; Manokeesic, Gary; Goodman, Starsky; Hanley, Anthony (Frontiers in Endocrinology, 2013)
The Sandy Lake Health and Diabetes Project (SLHDP) was initiated in 1991 as a partnership between Sandy Lake First Nation and researchers interested in addressing the high rates of type 2 diabetes mellitus (T2DM) in the community. Following the expressed wishes of the community, the SLHDP has encompassed a variety of community-wide interventions and activities including: community surveys to document T2DM prevalence and risk factors, the Northern Store program aimed at increasing the availability and knowledge of healthy food options, a home visit program for the prevention and management of T2DM, a local diabetes radio show, a school diabetes curriculum for grades 3 and 4, a community-wide walking trail to encourage increased physical activity, youth diabetes summer camps, and a variety of community events focusing on nutrition and physical activity. Over the twenty-two year existence of the SLHDP, the community has taken ownership of the program and activities have evolved in alignment with community needs and priorities. This paper discusses the history, implementation, evaluation and outcomes of the SLHDP and describes its sustainability. The SLHDP is a model of culturally appropriate participatory research that is iterative, with reciprocal capacity building for both key community stakeholders and academic partners.